El debate político decimonónico en la periodística de Jaume Balmes - Arroyo Cabello, María (Historia y Comunicación Social, 2010)
The XIX century is the century of journalism and freedom of the press, of the political journalist and the parliamentary journalist. Usually, the old-fashioned press is a press of opinions, ideological, party orientated; but also a mass media of ideas, an instrument to refute contrary ideas, promote the consensus or try to change the political system. In this context, the writer and journalist Jaume Balmes contributes to public discussion with a proposal of national reconciliation. And he does it using persuasive rhetorical appeals and a serene, journalism of argumentation which is the most important example of doctrinal journalism in Spain.